2007
DOI: 10.1086/521194
|View full text |Cite
|
Sign up to set email alerts
|

A Reservoir ofMoraxella catarrhalisin Human Pharyngeal Lymphoid Tissue

Abstract: Colonization by M. catarrhalis is more frequent than is determined by surface culture, because the organism resides both within and beneath the epithelium and invades host cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 46 publications
1
53
1
Order By: Relevance
“…FISH is extremely sensitive, and Heiniger et al found it had the highest detection rate of M. catarrhalis in clinical samples, exhibiting a higher rate than surface culture, PCR, or immunohistochemistry (33). Although our results using quantitative FISH analysis supported the trend of more H. influenzae in COM, it did not show significant differences between the patient groups.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…FISH is extremely sensitive, and Heiniger et al found it had the highest detection rate of M. catarrhalis in clinical samples, exhibiting a higher rate than surface culture, PCR, or immunohistochemistry (33). Although our results using quantitative FISH analysis supported the trend of more H. influenzae in COM, it did not show significant differences between the patient groups.…”
Section: Discussioncontrasting
confidence: 74%
“…Specifically, adhesins, pili, and lipooligosaccharides associated with H. influenzae lead to the attachment and invasion of cultured human epithelial cells via diverse pathways (41,60,63). M. catarrhalis has been shown to colonize and invade pharyngeal epithelial cells (45,59), and intracellular M. catarrhalis was specifically found in adenoids and tonsils (33). Intracellular S. aureus was demonstrated in nasal epithelium from patients treated for CRS (12,62).…”
Section: Discussionmentioning
confidence: 99%
“…Spaniol et al (141) also utilized host-specific inhibitors to study invasion and showed that invasion was dependent on clathrin polymerization, which seemed to contradict the earlier findings of Slevogt et al (138). Furthermore, actin polymerization was also found to contribute to the invasion process, and antibodies directed to fibronectin and integrin ␣5␤1 were able to inhibit invasion (141 (62). At the present, the exact mechanism of epithelial cell invasion by M. catarrhalis is not fully understood, but it appears to be an active process involving several host cell and bacterial mechanisms.…”
Section: Invasion Of the Host Epitheliummentioning
confidence: 99%
“…However, both alveolar macrophages (44) and neutrophils (45) from COPD patients have a defective ability to phagocytize respiratory pathogens. Dysfunction of leukocytes could promote bacterial persistence in the lung, resulting in acute exacerbations of COPD (46). The detection of COMP in alveolar macrophages and/or monocytes led us to test whether it could inhibit phagocytic killing of M. catarrhalis by human neutrophils.…”
Section: Discussionmentioning
confidence: 99%